Developing training intelligence in interdisciplinary performance teams: Perspectives from elite track cycling - Stadnyk, A.; Impellizzeri, F.; Stanley, J.; Menaspà, P.; Slattery, K. (Journal of Science and Cycling, 2024)
Introduction The effectiveness of sport scientists and performance staff in elite cycling often depends on their ability to complement the wider performance team - consisting of the cyclists, coaches, and other interdisciplinary practitioners - to support athlete development. A practitioner`s impact on athlete development and performance may be moderated by their ability to implement their knowledge and expertise, which itself can be constrained by several factors within the high performance sport environment. The aim of this study was to qualitatively examine elite track cycling coaches` perspectives of how practitioners can best support cyclists and their coaches through the implementation of sport science and research in practice to optimise training and performance.